2016
DOI: 10.3390/su8080751
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Assessment of the Infiltration Capacity Reduction in Clogged Porous Mixture Surfaces

Abstract: Permeable pavements have been used widely across the world to manage urban stormwater. The hydrological behaviour of permeable surfaces is a complex process affected by many factors, such as rainfall intensity, rainfall duration, pavement geometrical conditions, and clogging level of the permeable surface, amongst others. This laboratory study was carried out to assess the influence of clogging level and rainfall intensity on the infiltration capacity of porous mixture surfaces used in Permeable Pavement Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 39 publications
(62 reference statements)
3
29
1
1
Order By: Relevance
“…With the development of Chinese sponge city construction, PC will be widely applied in road structure [13]. Therefore, PC is of great significance for mitigating climate change, solving urban problems, and promoting the development of human society [14][15][16].The main properties of PC are strength, permeability, and durability. A porous structure is the key feature of PC, and porosity is the most important factor influencing mechanical strength, permeability, and durability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of Chinese sponge city construction, PC will be widely applied in road structure [13]. Therefore, PC is of great significance for mitigating climate change, solving urban problems, and promoting the development of human society [14][15][16].The main properties of PC are strength, permeability, and durability. A porous structure is the key feature of PC, and porosity is the most important factor influencing mechanical strength, permeability, and durability.…”
mentioning
confidence: 99%
“…With the development of Chinese sponge city construction, PC will be widely applied in road structure [13]. Therefore, PC is of great significance for mitigating climate change, solving urban problems, and promoting the development of human society [14][15][16].…”
mentioning
confidence: 99%
“…The studies reviewed above demonstrate the wide variety of findings that are possible from different investigations related to the hydraulic properties of permeable pavements. While studies have shown that the pavement performance-in terms of clogging-is dependent on a number of parameters [9,13,[15][16][17]20,21], there are no established test procedures or standardized methods for evaluating the hydraulic capacity of a permeable pavement, especially in laboratory models [5,9]. This is particularly evident from the three pieces of literature widely reviewed here.…”
Section: Equipment Developmentmentioning
confidence: 90%
“…Many field and laboratory investigations have been made regarding the clogging dynamics of permeable pavements. The long-term performance associated with particle clogging is typically influenced by a wide range of factors and local conditions, including pavement type and design [22][23][24]. Laboratory assessments conducted by Andrés-Valeri et al [22] indicated that porous concrete pavement showed less clogging potential than porous asphalt pavement due to its higher infiltration capacity and recovery from clogging.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term performance associated with particle clogging is typically influenced by a wide range of factors and local conditions, including pavement type and design [22][23][24]. Laboratory assessments conducted by Andrés-Valeri et al [22] indicated that porous concrete pavement showed less clogging potential than porous asphalt pavement due to its higher infiltration capacity and recovery from clogging. In another laboratory study [23] it was observed that particle clogging occurred on the surface for porous asphalt and on the geotextile for Hydrapave ® after 12 years of stormwater simulation, whereas Permapave ® showed no clogging even after 26 years.…”
Section: Introductionmentioning
confidence: 99%